Role of cytochrome P450 2D6 genetic polymorphism in carvedilol hydroxylation in vitro - Wang, Zhe (Drug Des Devel Ther, 2016)
Cytochrome P450 2D6 (CYP2D6) is a highly polymorphic enzyme that catalyzes the metabolism of a great number of therapeutic drugs. Up to now, >100 allelic variants of CYP2D6 have been reported. Recently, we identified 22 novel variants in the Chinese population in these variants. The purpose of this study was to examine the enzymatic activity of the variants toward the CYP2D6 substrate carvedilol in vitro. The CYP2D6 proteins, including CYP2D6.1 (wild type), CYP2D6.2, CYP2D6.10, and 22 other novel CYP2D6 variants, were expressed from insect microsomes and incubated with carvedilol ranging from 1.0 μM to 50 μM at 37°C for 30 minutes. After termination, the carvedilol metabolites were extracted and detected using ultra-performance liquid chromatography tandem mass-spectrometry. Among the 24 CYP2D6 variants, CYP2D6.92 and CYP2D6.96 were catalytically inactive and the remaining 22 variants exhibited significantly decreased intrinsic clearance values (ranging from ~25% to 95%) compared with CYP2D6.1. The present data in vitro suggest that the newly found variants significantly reduced catalytic activities compared with CYP2D6.1. Given that CYP2D6 protein activities could affect carvedilol plasma levels, these findings are greatly relevant to personalized medicine.